Time series (2017-2018) of dissolved trace metals, macro-nutrients, major elements and Pb isotopes in the Gulf of Aqaba, Red Sea - Benaltabet, Tal; Steiner, Zvi; Lapid, Gil; Torfstein, Adi (PANGAEA, 2023)
This dataset contains concentrations of dissolved trace metals (Al, Mn, Co, Ni, Cu, Zn, Cd, and Pb), macro-nutrients (Si and PO4), major elements (Li, Ca, K, Mg, and Sr) and Pb isotope compositions (206Pb/207Pb, 208Pb/206Pb) from a time-series station (Station A, ~700 m water depth) at the Gulf of Aqaba, northern Red Sea. Vertical water column profiles were collected between January 2017 and November 2018 on a monthly-daily resolution as part of the GEOTRACES REDMAST campaign. Seawater samples were collected using GO-Flo bottles, filtered (0.2 µm) and acidified to pH<1.8. Samples for trace metal concentrations and Pb isotopes were pre-concentrated using the the NOBIAS chelate PA-1 resin and measured using an Agilent 7500cx Magnetic Sector ICP-MS and a Thermo-Scientific Neptune Plus Multi Collector ICP-MS, respectively (Benaltabet, T., Lapid, G., & Torfstein, A. (2020). Seawater Pb concentration and isotopic composition response to daily time scale dust storms in the Gulf of Aqaba, Red Sea. Marine Chemistry, 227, 103895.‏). Macro-nutrient concentrations were measured using a Flow Injection Quik-Chem 8500 Auto-analyzer (Grasshoff, K., Kremling, K., & Ehrhardt, M. (Eds.). (2009). Methods of seawater analysis. John Wiley & Sons.‏). Major elements were analyzed as their ratio to Na by sample-standard bracketing using an Agilent Technology Varian-720 ICP-OES (Steiner, Z., Turchyn, A. V., Harpaz, E., & Silverman, J. (2018). Water chemistry reveals a significant decline in coral calcification rates in the southern Red Sea. Nature communications, 9(1), 3615.‏).
Keywords: GEOTRACES; isotope compositions; macronutrients; major elements; oceanographic time series; Pb isotopes; Red Sea; seawater; trace metals